2010
DOI: 10.1063/1.3503772
|View full text |Cite
|
Sign up to set email alerts
|

Flute instability and the associated radial transport in the tandem mirror with a divertor mirror cell

Abstract: The flute instability and the associated radial transport are investigated in the tandem mirror with a divertor mirror cell ͑the GAMMA10 A-divertor͒ with help of computer simulation, where GAMMA10 is introduced ͓Inutake et al., Phys. Rev. Lett. 55, 939 ͑1985͔͒. The basic equations used in the simulation were derived on the assumption of an axisymmetric magnetic field. So the high plasma pressure in a nonaxisymmetric minimum-B anchor mirror cell, which is important for the flute mode stability, is taken into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…(1) exactly in the non-paraxial divertor mirror. The results in the present paper revealed that the linear phase of the flute instability was almost the same as those in the previous works [4,7].…”
Section: Summary and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…(1) exactly in the non-paraxial divertor mirror. The results in the present paper revealed that the linear phase of the flute instability was almost the same as those in the previous works [4,7].…”
Section: Summary and Discussionsupporting
confidence: 80%
“…9 in the GAMMA10 A-divertor magnetic geometry, where the computer simulation was performed by solving Eqs. (5)- (8) with the initial conditions of D E (x) = 1, T E (x) = 1 [7]. Figure 9 is the radial profiles of D E and T E in the quasi-steady state, where plasma continues to be lost radially by the classical transport.…”
Section: Numerical Results Of M = 1 Flute Modementioning
confidence: 99%
See 1 more Smart Citation
“…Here p is the plasma pressure, γ is the specific heat index, U ≡ dχ/B 2 is the magnetic specific volume, where B is the magnetic field, the coordinate χ is defined as B = ∇χ, and the integration is carried out along a magnetic field line. Noting that ∇(pU γ ) • ∇U = U γ (∇p • ∇U + γp|∇U | 2 /U ), the interchange mode is stabilized by the good magnetic field line curvature in the case of ∇p •∇U 0, while the interchange mode is stabilized by the plasma compression in the case of ∇p • ∇U < 0 but ∇p • ∇U + γp|∇U | 2 /U 0 [5][6][7][8]. Here ∇U = −2 κ dχ/B 2 in the vacuum magnetic field, where κ is the magnetic field line curvature vector with the relation ∇B = Bκ [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, recently the original purpose of installing a magnetic divertor has been changed to be one of performing the simulation experiments of the divertor in the closed system. Thus the investigation of transport on the GAMMA10 A-divertor is in progress [3][4][5]. The study of ion orbits in the divertor and dipole regions is a part of the investigation of the GAMMA10 A-divertor with the aim of plasma wall interaction.…”
Section: Introductionmentioning
confidence: 99%